Local Analysis of The Padeye-Brace Clamp Structure Strength during Installation of Riser-Spool at Offshore Platform - Rudi Walujo Prastianto; Yusapril Hagie Syamsun Nahar; Yoyok Setyo Hadiwidodo (International Journal of Offshore and Coastal Engineering, 2023)
The need for natural gas in Indonesia has developed very rapidly, thus encouraging the construction of many production support facilities. One of them is the Wellhead Platform B (WHP-B) in West Pangkah waters, East Java. This production platform is in shallow water conditions with a depth of less than 5 m and a distance of less than 5 km from the shoreline. Therefore, when the pipe installation process is carried out, a crane barge or construction vessel type cannot be used. To be able to connect the gas flow from the well to the production platform (WHP-B), it requires a supporting structure in the form of a spool and riser. The size of the spool and riser that will be installed on WHP-B is 16” and 6” with the condition that the riser and spool are connected. A crawler crane carried by a barge can be used for the installation process to occur efficiently. For the 16”-6” riserspool to be lowered simultaneously, it requires a temporary structure that serves to clamp the two pipes so that they can be installed simultaneously. This structure is a modification between the padeye and the brace clamp. The process of lowering the 16”- 6” riser-spool experienced a critical condition when it was in the splash zone. Based on the global analysis results, it is known that the UC that occurs is 0.97 with a vertical bending stress of 172.36 MPa in the 3rd padeye-brace clamp structure. After conducting local analysis on the 3rd brace clamp, it is known that the clamp structure is still in a safe condition with a maximum von Mises stress of 2.42 MPa and a maximum deformation of 0.0096 cm.